Effects of magnesium, boron and molybdenum on symbiotic nitrogen fixation of beans (Phaseolus vulgaris L.) - Ruschel, Alaides Puppin; Britto, Dirce Pinto Pacca de Souza; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2024)
In the present paper, effects of magnesium, boron and molybdenum on symbiotic nitrogen fixation of beans (Phaseolus vulgaris) were studied in acid soil, with and without liming. Two greenhouse experiments were carried out in randomised complete blocks, the following conclusions were drawn: 1. There was a pronounced effect of liming which increased nodule numbers more than plant growth. 2. Magnesium increased nodule numbers only. 3. Boron effects were dependent on the calcium applications. In the first experiment, where lime was not applied adequately, 5 kg/ha of H3BO3 reduced plant growth. In the second experiment 3,75 kg/ha of H3BO3 increased nitrogen fixation and plant growth, but in the limed treatments only. More boron was necessary for optimal nodulation than for plant growth. 4. Molybdenum decreased nodule numbers, increasing at the same time the amount of nitrogen fixed per nodule.